The Irish kelp, Fucus vesiculosus, a highly potential green bio sorbent for Cd (II) removal: Mechanism, quantitative and qualitative approaches. (10th December 2021) - Brinza, Loredana; Geraki, Kalotina; Matamoros-Veloza, Adriana; Ignat, Maria; Neamtu, Mariana
Abstract: Looking for new green and environmentally friendly bio sorbents for metal removal from polluted wastewater, the present study investigates the potential new bio sorbent for Cd(II) removal from wastewater namely, the mechanism and uptake capacity of Cd(II) by brown algae, Fucus vesiculosus from the Irish Sea. This work takes a comprehensive approach involving the combination of qualitative and quantitative information collected from macro to atomistic scale, in a direct and non-destructive manner. Our results demonstrate that Cd(II) is adsorbed on the algal surface based on carboxylic of alginate groups. Effective Cd(II) adsorption is achieved at pH conditions between 5 and 7, at which the uptake occurs rapidly (∼2 h), with increasing Cd(II) concentration. Cd maximum uptake capacity (i.e., 1.203 mmol Cd g −1 dried algae) in first adsorption cycle show superior uptake as opposed to other species. Quantitatively the bio sorbent has an increasing uptake capacity (more than two folds) in the second cycle, after metal elution and biomass surface sites functioning. Desorption of Cd(II) and the regeneration of the biomass is effectively achieved with HCl (10 mM) and EDTA (1 mM), but they can only be used for two cycles, before the efficiency decreases. Microprecipitation occurs at high pH (>9) when using NaOH as an eluent. Results from this work shed new light on understanding Cd(II) binding mechanisms on Fucus v ., providing crucial information for further process optimization, pilot testing, scaling up and implementation as a clean, environmentally friendly biotechnology applied to wastewater treatments.